Polaris Battery Labs : startup risk management - Walker, Russell, 1972-; Dilts, Andrew (London : Kellogg School of Management, 2018)
Polaris Battery Labs was an Oregon-based startup that provided innovation services to companies in the lithium ion battery industry. Its operating philosophy and expertise in this fast-growing industry enabled it to provide great value to its clients, but as a startup that was seeking growth the company was subject to multiple risks.
Originally Published InWalker, R., & Dilts, A. (2018). Polaris Battery Labs: Startup risk management. 5-118-005. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Polaris Battery Labs; New business enterprises -- Oregon; Risk management -- Oregon; Lithium ion batteries